Вплив Galega orientalis Lam. на екологічну рівновагу ґрунту в зв’язку з інтродукцією його в Лісостепу України - Abramov, A.A. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 1999)
Agroecological character Galega orientalis Lam. new long-term leguminous culture in connection with introduction in Forest-Steppe of Ukraine is investigated. Its advantages before traditional cultures is established.